PENGARUH INSEKTISIDA TERHADAP KEMAMPUAN ADAPTASI WERENG BATANG COKELAT (NILAPARVATA LUGENS STAL) PADA PADI VARIETAS TAHAN - Iswanto, Eko Hari (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2019)
Effect of Insecticides to Brown Planthopper (Nilaparvata lugens Stal) Adaptation on Resistant Rice Varieties. Brown planthopper (BPH) (Hemiptera: Delpachidae) is one of major pests on rice cultivation in Indonesia. Resistant rice varieties and insecticides are commonly used by farmers in BPH management. But, BPH can rapidly adapt on long-term planted varieties and insecticide. The aim of research was to study the ability of insecticide resistance BPH in adaptation on resistant rice varieties. This study was conducted at Indonesian Center for Rice Research from October 2018 to June 2019. BPH?s were collected from farmer field and reared for 6th generation. BPH?s were divided into four insecticide population. BPH population sprayed each generation by BPMC (BPMC-BPH), imidacloprid (imidacloprid-BPH), pymetrozine (pymetrozine-BPH), and unsprayed (Control-BPH). In first generation, insecticide resistance conducted to obtain baseline data of BPH resistance to imidacloprid, BPMC and pymetrozine. On 6th generation, insecticide resistance test repeated to each population. Four BPH population were tested for the survival rate, fecundity, amount of honeydew, and rice varieties reaction. Result showed that Field population 1st generation were resistance to BPMC and imidacloprid with Resistance Factor (RF) 4.1 and 13.5-fold, respectively, while to pymetrozine was indicate resistance (RF 3.7-fold). In 6th generation, LC50 all insecticide population were increased, while in Control-BPH were decreased. Inpari 13 still effective againts BPH in all test results. Insecticide resistance-BPH tend to lower adaptation on resistant variety than insecticide susceptible-BPH.